Russia's Security Perceptions and Arctic Governance - Borozna, Angela (Politics and Governance, 2024)
Russia's war in Ukraine further strained Russia's relations with the West and negatively influenced Arctic regional governance, especially after seven members of the Arctic Council paused cooperation with Russia. The rationale of the suspension was to express disapproval by seven Arctic states of Russia's aggression in Ukraine. However, the suspension of cooperation with Russia within the Arctic Council format prompted some observers to question the relevance and utility of the institution. Russia never expressed its wish to leave the Council and continues to express its desire for multilateral cooperation in the region. This raises the question: Can Russia's assertive stance in Ukraine coexist with peaceful cooperation in the Arctic? In order to answer this question, this article addresses the following questions: How does the geopolitical tension shape Russia's approach to Arctic governance? And what is the role of military and economic security in Russia's Arctic policy? The article uses a comparative method combined with discourse analysis to establish a change in Russia's view on Arctic governance before and after the war in Ukraine.